Tadeusz Nowak: „przez kolędę” (wyobraźnia) - Jarzyna, Anita (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The article shows the importance of a Christmas carol in the poetic imagination of Tadeusz Nowak. First of all is the presence of a word carol itself, especially because many poems, titled carol are not even connected with the carol’s motives. Then it’s vital, how Nowak is referring to traditional carols and how he is reinterpreting typical themes connected with it, such as: annunciation, motherhood (and parenthood generally), relation between man and animals, identity of the Other, of someone, who (like Jesus, Holly Family) is different than everybody else. It turns out that words specifically connected with carol like: hay, the Star of Bethlehem, Christmas eve, chorus from polish folk song hej kolęda, kolęda are part of his language, he uses them to describe his world, apart from idyllic associations, even apart from Christmas context.